Indonesia Administrative E-Court Regulation Toward Digitalization And E-Government - Aju Putrijanti; Kadek Cahya Susila Wibawa (Fakultas Hukum Universitas Mataram, 2021)
E-court regulation in Indonesia legalized in order to follow and adjust the digitalization, modernization and globalization. Administrative Court is judiciary body which has to implement the e-court. The object is to analyse the implementation of e-court towards e-governmnet..The method use to analyze is normative juridical research, study the documents (regulation), and secondary data are journals, opinion from experts. The issues are the implementation of administrative e-court in Indonesia towards the development of e-government. The implementation of administrative e-court can not fully implemented because there is legal interpretation in Supreme Court Regulation Number 1 Year 2019 of Case Administration and Court Electronically, there is no regulation of implementation for both process. There is inconsistency between Article number 24 and 25 of Supreme Court Regulation, for evidenciary process follows regulations for each procedural system. The development e-government has shows good effort, whereas it still need to improve. There should be a new regulations to substitute Perma, and to harmonize with the regulations of Administrative Court in future. The implementation of Administrative e-court is absolutely carried out in the digital era. It is to support the realization of e-government.